ANALISIS PEMANFAATAN E-COMMERCE UNTUK MENINGKATKAN DAYA SAINGUMKM KOTA BENGKULU ( STUDI DI UMKM KELURAHAN NUSA INDAH ) - Chairunisa indri rahmatika; Andang sunarto; Andi harpepen (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the use of e-commerce in improving the competitiveness of Micro, Small, and Medium Enterprises (UMKM) in Nusa Indah Village, Bengkulu City. The development of information and communication technology has driven a shift in marketing patterns from conventional to digital, making e-commerce an importantstrategy for UMKM to expand market reach, improve cost efficiency, and strengthen their competitive position. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation of UMKM actors in the research area. The results show that some UMKM have utilized e-commerce through social media and marketplaces as a means of promotion and sales. This utilization has had a positive impact in the form of increased product visibility, easier consumer access, and wider market opportunities. However, there are such as limited digital literacy, minimal human resources, and a lack of understanding of effective digital marketing strategies. Therefore, support from thegovernment, related institutions, and ongoing training are needed so that the use of e-commerce can be optimized and can increase the competitiveness of UMKM in Nusa Indah Village in a sustainable manner.